العوامل المؤثرة على أسعار الأسهم في السوق المالية السعودية - أحمد يوسف, أحمد هاشم (Gezira Journal of Economic and Social Sciences, 2020)
هدفت هذه الدراسة إلى تحديد أثر كل من العائد على السهم، والقيمة الدفترية للسهم، ومضاعف ربحية السهم، ومكرر السعر، ومعدل دوران السهم على القيمة السوقية لأسهم الشركات المدرجة في سوق المالية السعودية. اعتمدت الدراسة على كل من المنهج الاستنباطي والاستقرائي والتاريخي. بلغ حجم مجتمع الدراسة (128) شركة بينما بلغ حجم عينة الدراسة (60) شركة تم اختيارها باستخدام أسلوب العينة العشوائية البسيطة. بينت نتائج الدراسة وجود علاقة ذات دلالة إحصائية بين كل من القيمة الدفترية للسهم، ومضاعف الربحية، والعائد على السهم والقيمة السوقية للسهم، كما أوضحت نتائج الدراسة عدم وجود علاقة ذات دلالة إحصائية بين كل من مضاعف ربحية السهم ومعدل دوران السهم وبين القيمة السوقية للسهم، توصلت الدراسة لعدة توصيات للمستثمر السعودي منها ضرورة مراعاة سيولة السهم من خلال الاهتمام بمضاعف ربحية السهم عند اتخاذ قرار الاستثمار في الأسهم وذلك بالرغم من توفر السيولة من المصادر الأخرى.     The purpose of this study is to identify the impact of earnings per share, book value per share, market price/earnings per Share, market price /book value and share turnover rate on the market price per share in the Saudi Stock Market. The study adopt deductive, inductive and historical methods. The population of the study included the (128) listed companies in the Saudi Stock Market. A random sample of (60) companies was withdrawn. The results of the study confirmed that there was a significant statistical relationship between book value per share, market price/earnings per share, earnings per share and the market price per share. As for the price earnings, and share turnover rate the results showed insignificant statistical relationship with the market price per share, researcher recommended a several recommendations such as the Saudi investor should take into account the liquidity of the stock by paying attention to the earnings per share when making the investment decision, despite the availability of liquidity from other sources.